Radiobiological quantities in proton-therapy: Estimation and validation using Geant4-based Monte Carlo simulations - Petringa, G; Romano, F; Manti, L; Pandola, L; Attili, A; Cammarata, F; Cuttone, G; Forte, G; Manganaro, L; Pipek, J; Pisciotta, P; Russo, G; et al. (Physica medica, 2019)
PURPOSE: The Geant4 Monte Carlo simulation toolkit was used to reproduce radiobiological parameters measured by irradiating three different cancerous cell lines with monochromatic and clinical proton beams. METHODS: The experimental set-up adopted for irradiations was fully simulated with a dedicated open-source Geant4 application. Cells survival fractions was calculated coupling the Geant4 simulations with two analytical radiobiological models: one based on the LEM (Local Effect Model) approach and the other on a semi-empirical parameterisation. Results was evaluated and compared with experimental data. RESULTS AND CONCLUSIONS: The results demonstrated the Geant4 ability to reproduce radiobiological quantities for different cell lines.
Keywords: Radiobiological model; Geant4; Radiobiology; radiobiologie; Cell Line, Tumor; celková dávka radioterapie; RBE; Proton; Proton Therapy; Survival fraction; reprodukovatelnost výsledků; Reproducibility of Results; Radiotherapy Dosage; lidé; Monte Carlo Method; Humans; metoda Monte Carlo; Radiotherapy; protonová terapie; nádorové buněčné linie; Monte Carlo